DYNAMICS OF UKRAINIAN POPULATION LEVEL IN THE CONDITIONS OF SUSTAINABLE DEVELOPMENT AND THE EMERGENCE OF THE MODERN MARKET RELATIONS - Kovalchuk, T. O. (Science and Transport Progress, 2009)
The system of indexes characterizing the standard of living is considered and analyzed: average monthly and minimum wages, living wage, indexes of consumption, housing and property position of population, amount of free social services given by the state. The trends of progress, features of the state and forming of living level of population of Ukraine are exposed.